Bis(azido)palladium(II) Complexes Bearing an (R or S)‐(BINAP) Ligand: Synthesis, Structures, and Catalytic Application to Suzuki–Miyaura C─C Coupling Reactions. (27th December 2019) - Choi, Sun Myeong; Lee, Sera; Kim, Yong‐Joo; Lee, Ji Hun; Lee, Soon W.; Choi, Jun‐Chul
Abstract : Suzuki‐Miyaura C‐C coupling using BINAP‐Pd(II) azide.